Manajemen risiko teknologi informasi pada PT. XYZ menggunakan framework COBIT 5 - Maharani, Mutia; Klasmanto, Andreas; Simanjuntak, Bima Aprianto; Andayani, Sri (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
PT. XYZ applies Information Technology in business processes to achieve company goals. achieve company goals. However the use of Technology brings risks that can reduce business effectiveness and efficiency of the business. PT. XYZ faced several problems in its IT department, including network connectivity issues, human error, hardware failure, ERP system integration failure, data security, and human error, hardware failure, ERP system integration failure, data security, data backup failures, system downtime, and power outages. This research applies data collection methods through interviews and risk analysis, evaluating the steps taken by the company in managing IT risks systematically. Research results show that the application of the COBIT 5 Framework is effective in identifying, assessing, and managing IT risks, thus helping the company to minimize losses and ensure smooth operations. This research provides recommendations for improved risk management that is more structured and data-driven risk management, as well as the importance of training for IT staff to improve risk management capabilities in the company. improve risk management capabilities in the company.